Análisis a los estados financieros de la Cooperativa de Ahorro y Crédito Tena Ltda. de la ciudad del Tena, provincia de Napo, correspondiente al periodo 2012, 2013 - Moran Iglesias, María Narciza (2015)
Was carried Financial interpretation to the Financial Statements of the Cooperative Savings and Credit Tena Ltda., In the province of Napo, with the aim of studying the results obtained during the periods 2012 to 2013 and thus determine the economic situation of the aforementioned cooperative to give a correct decision making by managers. For which different methods of financial analysis being these the horizontal method which agreed to perform the respective comparisons of both assets , liabilities and equity for the years 2012 and 2013 in a studio and it required the use of the balance sheet was applied and statements of income , also the vertical method was used to determine the percentage share of each of the accounts in order to determine which account is the one with greater intervention and concluded that it is the loan portfolio. Then certain financial ratios such as liquidity, leverage and profitability which indicated the economic and financial position that is the aforementioned Savings and Credit Cooperative is used. The result obtained in the investigation discloses favorable and unfavorable situations that arise in the accounts leading to the implementation of corrective measures by formulating recommendations that improves the proper use of economic resources and prevent scenarios occur they can affect the survival of the aforementioned financial institution, by implementing appropriate internal controls